(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Mental illness is known to be difficult to diagnose and we can say that if someone has a mental illness, it can affect someone for years before diagnosis. Geriatricians often encounter a large number of patients for treatment without being able to reduce or automatically diagnose them. Designing a system to help better to diagnose this disease and to reduce cost and time is our aim in this study. We used a mental dataset applied with data mining optimization algorithms and we applied it with the Python programing language, including training the test split and pre-processing feature selection model used random forest (RFE) and feature importance to enhance the system results and accuracy for mental dataset in our research and processed the missing values that found with attributes.The best accuracy was achieved by Adaboost optimization model, which gave us 99% accuracy and the Adaboost ensemble merged with the decision tree produced a 94% accuracy. Moreover, the random forest optimization produced better accuracy at 96% and 92% resulted from using the SVM algorithm. Finally, this optimization system by merging the two algorithms to work together will be more efficient and better able to help classify and diagnose suffering patients using a huge amount of data in little time and at low cost.